Employee Performance: Is Mediation by Innovation Possible? - Ronnie Masman (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2026)
The construction services sector plays a crucial role in boosting Indonesia's economic growth. The object of this study is a construction services company operating in Java, which currently has approximately 200 employees spread across various projects and locations. This study examines the factors influencing employee performance, including organizational citizenship behavior, competitive intensity, and organizational slack, each mediated by innovation, particularly those related to employee performance in construction services companies. The results of this study indicate that all hypotheses have a positive and significant influence, except for the fifth hypothesis, which is rejected because there is no significant influence between the level of competitive intensity and employee performance.